Benjamin and Adorno on Art and Art Criticism : Critique of Art - Lijster, Thijs, 1981- (Book collections on Project MUSE., 2017)
"This book brings together two of the most important figures of twentieth-century criticism, Walter Benjamin and Theodor Adorno, to consider a topic that was central to their thinking: the place of and reason for art in society and culture. Thijs Lijster takes us through points of agreement and disagreement between the two on such key topics as the relationship between art and historical experience, between avant-garde art and mass culture, and between the intellectual and the public. He also addresses the continuing relevance of Benjamin and Adorno to ongoing debates in contemporary aesthetics, such as the end of art, the historical meaning of art, and the role of the critic."--Provided by publisher